Polskie książki z historii oświaty i wychowania (1945–1989) w ocenie ówczesnej krytyki - Wnęk, Jan (Biuletyn Historii Wychowania, 2014)
This article analyses the reviews of Polish books on the history of education and bringing up children in the years 1945-1989. It presents the ways in which critics reviewed new publications and shows the aspects which they paid special attention to. The reviews were published in the most renowned magazines among historians of education and raising children, such as ”Przegląd Historyczno-Oświatowy” (The History and Education Review), ”Rozprawy z Dziejów Oświaty” (Dissertations on the History of Education). Some of them were written by renowned specialists in the field. For contemporary historians, the reviews may constitute an interesting source of information on academic criticism from the times of the Polish People’s Republic. They may also bear witness to the hard work and efforts made towards conducting thorough studies into the history of education and bringing up children over various historical periods.